Efectividad de la inversión pública financiada por el FONCOMUN sobre el desempeño social y económico de la región Loreto periodo 2013 – 2022 - Pan Santillan, Helen Pierina (2025)
This research analyzed the effectiveness of public investment financed by Municipal Compensation Fund (FONCOMUN) on the economic and social performance of the Loreto region during the 2013-2022 period, using a quantitative methodology and econometric regression models. The results showed that public investment through FONCOMUN has a positive and statistically significant effect on the region's economic performance, with an elasticity of 0.17, although it only explains 55.64% of its variability. In contrast, no significant relationship was found between such investment and social performance, measured through INCORE, with a low determination coefficient of 10.29%. These findings suggest the need to strategically reorient FONCOMUN resources to amplify their economic impact and strengthen their social management mechanisms, establishing an integrated investment planning system that maximizes both economic and social impact in the region.